Antiamoebic and Cytotoxicity of Ethanolic leaves Extract of Acacia nilotica (L) - Ahmed Saeed Kabbashi; Mohammed Ismail Garbi (Al Ameen Medical College, 2015)
Background: Acacia nilotica (L) related to family Fabaceae-Mimosoideae. The division of Acacia nilotica is Magnolophyta and class is Magnolipsida. The genus is Acacia and species is nilotica. The ailments treated by this plant include colds, congestion, fever, gallbladder, hemorrhage, hemorrhoids, leucorrhoea, ophthalmic, sclerosis and small pox. Acacia bark is drunk for intestinal pains and used for treating acute diarrhea. Other preparations are used for gargle, toothache, ophthalmic and syphilitic ulcers. The roots of Acacia are used to treat Tuberculosis. The World Health Organization (WHO) estimates that the protozoan Entamoeba histolytica is a major cause of morbidity worldwide, causing approximately 50 million cases of dysentery and 100,000 deaths annually. Intestinal amoebiasis due to the infection of E. histolytica is ranked third on the list of parasitic protozoan infections leading to death behind malaria and schistosomiasis. Objectives: This study was carried out to evaluate antiamoebic activites (Entamoeba histolyica) and cytotoxicity (MTT assay) of ethanol extract of A. nilotica (leaves). Method: The extract of A. nilotica (leaves), with different concentration (500 ppm, 250 ppm and 125 ppm) and metronidazole concentration (312.5 μg/ml) to be investigated in vitro against Entamoeba histolyica trophozoites. And cytotoxicity (MTT assay) with different concentration (500 ppm, 250 ppm and 125 ppm) and compare triton-100 (the reference control). Result: The result was obtained from A. nilotica leaves ethanol extract which exhibited 100% mortality within 96 h, at a concentration 500 ppm; this was compared with Metronidazole which gave 96% inhibition at concentration 312.5 µg/ml at the same time. And MTT assay verified the safety of the examined extract. Conclusion: These studies conducted for both A. nilotica leaves was proved to have potent activities against Entamoeba histolyica trophozoites in vitro. And MTT assay verified the safety.